Incorporating biodiversity conservation in Peruvian development: A history with different episodes - Yves Zinngrebe (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2016)
Conservation movements in developing countries, such as Peru, arise in relation to predominant perceptions concerning development and progress. In the 1960s and 1970s, the Peruvian government adopted a development vision that promoted the colonisation of the Amazon region, which led to the expansion of agricultural, infrastructural and extractive projects. As a reaction to this development paradigm, citizens formed various conservationist groups to push the protection of biodiversity onto the political agenda. This article analyses how these different groups emerged and started to develop a discourse on biodiversity conservation. After conducting qualitative interviews with stakeholders, discourse groups were identified and described with regard to their historical appearance. For example, in the 1980s, a group of mainly biologists started forming NGOs and supporting projects in and around protected areas. Contrastingly, another group is looking at conservation as a traditional, cultural activity of indigenous people. With the ratification of the Convention for Biological Diversity (CBD) in the early 1990s, a new political momentum led to important legislative and institutional changes, which stood in contrast to the general development agenda of resource based growth. A new perspective started to enter the discourse with the creation of regional governments in 2002, which led to new practical questions about local biodiversity management. After studies like the Millennium Ecosystem report and the TEEB assessment (The Economics of Ecosystems and Biodiversity), economic approaches to biodiversity conservation initiated a new perspective on biodiversity policy. While those different discourse groups do not automatically contradict or exclude each other, this article sheds light on the different historical situations and motivations underlying these discourses.
Keywords: 330